Overexpression of the FBA and TPI genes promotes high production of HDMF in Zygosaccharomyces rouxii - Wang, Yanhong; Liu, Wei; Chen, Jingyao; Li, Zhijiang; Hu, Yijia; Fan, Zixiang; Yan, Liangyuan; Liu, Jiahui; Zhou, Yuao; Jiang, Wei; Rui, Haiying; Dai, Lingyan (Frontiers in Microbiology, 2024)
4-Hydroxy-2,5-dimethyl-3 (2H)-furanone (HDMF) is widely used in the food industry as a spice and flavoring agent with high market demand. In this study, fructose-1,6-bisphosphate aldolase (FBA) and triose phosphate isomerase (TPI) were overexpressed in Zygosaccharomyces rouxii in the form of single and double genes, respectively, via electroporation. High-yield HDMF engineered yeast strains were constructed by combining the analysis of gene expression levels obtained by real-time fluorescence quantitative PCR technology and HDMF production measured by HPLC. The results showed that there was a significant positive correlation between the production of HDMF and the expression levels of the FBA and TPI genes in yeast; the expression levels of the FBA and TPI genes were also positively correlated (P<0.05). Compared with the wild type (WT), the engineered strains F10-D, T17-D, and TF15-A showed marked increases in HDMF production and FBA and TPI genes expression (P<0.05) and exhibited great genetic stability with no obvious differences in biomass or colony morphology. In addition, the exogenous addition of D-fructose promoted the growth of Z. rouxii. Among the engineered strains, when fermented in YPD media supplemented with D-fructose for 5 days, TF15-A (overexpressing the FBA and TPI genes) generated the highest HDMF production of 13.39 mg/L, which is 1.91 times greater than that of the wild-type strain. The results above indicated that FBA and TPI, which are key enzymes involved in the process of HDMF biosynthesis by Z. rouxii, positively regulate the synthesis of HDMF at the transcriptional level. D-fructose can be used as a precursor for the biosynthesis of HDMF by engineered yeast in industrial production.